Answer:
1st, 2nd and 6th options
Explanation:
Given
- x +
= 6x ( multiply through by 6 to clear the fractions )
4 - 6x + 1 = 36x ← option 1 will have the same solution set
----------------------------------------------------------------------
Adding the 2 fractions on the left side gives
+
- x = 6x , that is
- x = 6x ← option 2 will have the same solution set
------------------------------------------------------------------------
From
4 - 6x + 1 = 36x ( add 6x to both sides )
5 = 42x ← option 6 will have the same solution set